2013
DOI: 10.1186/1752-0509-7-103
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism and glutamate-glutamine cycle in the brain: a stoichiometric modeling perspective

Abstract: BackgroundThe energetics of cerebral activity critically relies on the functional and metabolic interactions between neurons and astrocytes. Important open questions include the relation between neuronal versus astrocytic energy demand, glucose uptake and intercellular lactate transfer, as well as their dependence on the level of activity.ResultsWe have developed a large-scale, constraint-based network model of the metabolic partnership between astrocytes and glutamatergic neurons that allows for a quantitativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 67 publications
4
27
0
Order By: Relevance
“…However, this potential argument against AAT activity is invalid because of spatial separation between cytosolic glutamate formation and mitochondrial degradation, removal of synthesized glutamate by glutamine formation and of α-KG by TCA cycle activity as well as temporal separation during exposure to high and low extracellular glutamate concentrations shown by modeling. A recent study performing stoichiometric modeling concluded that the well-known increase in glycolysis compared to oxidative metabolism (decreased OGI) during brain activation can be partly (but not completely) explained by an increase in glutamate-glutamine cycling [108], with a doubling of cycle flux when the ratio between rates of oxidative and glycolytic metabolism decreases from 5.5 to 4.25. This indicates that cycle activity must vary greatly from moment to moment in concert with brain activation or lack thereof.…”
Section: Suggested Pathway For Coupled Formation and Oxidation Of mentioning
confidence: 99%
“…However, this potential argument against AAT activity is invalid because of spatial separation between cytosolic glutamate formation and mitochondrial degradation, removal of synthesized glutamate by glutamine formation and of α-KG by TCA cycle activity as well as temporal separation during exposure to high and low extracellular glutamate concentrations shown by modeling. A recent study performing stoichiometric modeling concluded that the well-known increase in glycolysis compared to oxidative metabolism (decreased OGI) during brain activation can be partly (but not completely) explained by an increase in glutamate-glutamine cycling [108], with a doubling of cycle flux when the ratio between rates of oxidative and glycolytic metabolism decreases from 5.5 to 4.25. This indicates that cycle activity must vary greatly from moment to moment in concert with brain activation or lack thereof.…”
Section: Suggested Pathway For Coupled Formation and Oxidation Of mentioning
confidence: 99%
“…A competing hypothesis, the neuron-to-astrocyte lactate shuttle (NALS) (Mangia et al, 2009), is based on a number of arguments that center on the different characteristics of GLUT1, the glucose transporter found on the epithelial cells of blood vessels and on astrocytes, and GLUT3, the transporter found mainly on the neuropil of neurons (Chih et al, 2001; Chih and Roberts, 2003; Mangia et al, 2009, 2011; Massucci et al, 2013). GLUT1 has a high affinity for glucose (Heyes, 2010) and is also capable of transporting other hexose at a much-reduced rate (Gould et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The transient increase in lactate level during exercise might be a consequence of energetic processes that complement healthy brain processes . The subsequent decrease in lactate concentration observed during the latter stages of strenuous activity imply that exercise‐induced fatigue may be due to depletion of an energy source; the lactate in neurons is further oxidized to produce glutamate . This metabolic process further increases the extracellular glutamate concentration.…”
Section: Discussionmentioning
confidence: 99%